Austria : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Selected Issues paper for Austria looks at the fiscal burden facing Austria owing to aging, and the policy steps necessary to address it. It gives a short description of the Austrian pension, health care, and long-term care systems, and describes how aging will affect the costs of these systems. It then analyzes the development of age-related spending and the sustainability of general government finances under different scenarios, and quantifies the primary adjustment required to keep public finances on a sustainable path in the long term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet